2001
DOI: 10.1074/jbc.m009710200
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of Annexin II Mediates Binding to F-actin

Abstract: Annexin II heterotetramer (AIIt) is a multifunctional Ca 2؉ -binding protein composed of two 11-kDa subunits and two annexin II subunits. The annexin II subunit contains the binding sites for anionic phospholipids, heparin, and F-actin, whereas the p11 subunit provides a regulatory function. The F-actin-binding site is presently unknown. In the present study we have utilized site-directed mutagenesis to create annexin II mutants with truncations in the C terminus of the molecule. Interestingly, a mutant annexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 51 publications
3
106
0
Order By: Relevance
“…Among a large number of PtdIns(4,5)P 2 -binding proteins, A2t is suited for this putative role due to its unique properties; i.e. A2t binds the membrane in a Ca 2ϩ -and/or PtdIns(4,5)P 2 -dependent manner (21,22), laterally aggregates on the membrane surface (14), interacts with F-actin (59), and is abundant in mammalian cells. Furthermore, recent reports have indicated the potential involvement of annexin A2 and A2t in regulation of membrane microdomain formation (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Among a large number of PtdIns(4,5)P 2 -binding proteins, A2t is suited for this putative role due to its unique properties; i.e. A2t binds the membrane in a Ca 2ϩ -and/or PtdIns(4,5)P 2 -dependent manner (21,22), laterally aggregates on the membrane surface (14), interacts with F-actin (59), and is abundant in mammalian cells. Furthermore, recent reports have indicated the potential involvement of annexin A2 and A2t in regulation of membrane microdomain formation (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…SNX17 resides in distinct parts of the early endosomal compartment and enhances the endocytosis rate of LDLR, and possibly of other surface receptors [25] . The A2IC faces the cytosol and is in ideal proximity to interact with the actin cytoskeleton within the cell [8] . In preclinical tumor models, it has been shown that therapeutic targeting of RPS2 is an excellent approach for the eradication of prostate cancer [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A2 is cleaved by chymotrypsin and plasmin into a 33 kDa C-terminal core domain and a 3 kDa N-terminal domain. The first 14 residues of the N-terminal domain contain a high-affinity binding site for S100A10, a Ca 2+ binding protein [8,10] (Figure 1). Annexin A2 interacts with S100A10 to form AA2t [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein has been implicated in numerous cellular processes; for example, aggregation of phospholipid vesicles (Blackwood & Ernst, 1990;Ayala-Sanmartin et al, 2001), G-actin polymerization Hayes et al, 2006), F-actin bundling (Filipenko & Waisman, 2001), apical lumen formation (Martin-Belmonte et al, 2007), endosome biogenesis (Morel et al, 2009), angiogenesis (Semov et al, 2005) and exocytosis (Lorusso et al, 2006;Umbrecht-Jenck et al, 2010). Additionally, several unique and diverse binding partners and ligands of AnxA2 have been identified, such as PCSK9 (Mayer et al, 2008), phosphatidylinositol 4,5-bisphosphate (Rescher et al, 2004), heparin , chlorotoxin (Kesavan et al, 2010) and progastrin (Singh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%